Examination of the Factor Structure and Correlates of the Perceived Military Healthcare Stressors Scale. Issue 1 (20th October 2020) - Hale, Willie J.; Moore, Brian A.; Straud, Casey L.; Baker, Monty T.; Peterson, Alan L.
Abstract: The current study evaluated the factor structure, reliability estimates, correlates, and predictive utility of the Perceived Military Healthcare Stressor Scale (PMHSS) in a sample of active duty military medical personnel ( N = 1, 131) deployed to Joint Base Balad in Iraq. The sample was composed of an approximately even split of male (51.2%) and female (48.8%) participants who ranged in age from 18 to 60 years. The PMHSS is a 21‐item measure that was designed to assess the impact of specific medical stressors that military healthcare providers may encounter while deployed. An exploratory factor analysis of the PMHSS revealed the presence of two distinct factors: trainable and futility stressors. Confirmatory factor analysis showed that a bifactor model best represented the data, with all items loading higher on the general factor relative to their specific subscale factors. Evidence of partial scalar invariance by gender was found. The PMHSS was significantly correlated with several convergent measures, including assessments of posttraumatic stress disorder (PTSD), depression severity, distress due to both combat exposure and general deployment‐related concerns, and positive affect, r s = .30–.59. PMHSS scores were more strongly correlated with PTSD and depression in women than in men, and they provided incremental validity in predicting convergent measures over and above other related constructs. Healthcare–specific stressors are an understudied area, and this study provides new insights into how deployment‐related caregiving stress may impact deployed military medical personnel independently of the impact of combat experiences. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐19‐0397.R2_Moore_cantonese Traditional Chinese 軍事醫療保健壓力感知量表的因素結構及其相關研究 摘要 : 本研究以部署在伊拉克巴拉德聯合基地的現役軍事醫務人員(N = 1, 131)為樣本, 評估了軍事醫療保健壓力感知量表(PMHSS)的因素結構、信度估計、相關性以及預測效用。該樣本由男性(51.2%)和女性(48.8%)組成, 年齡從18歲到60歲不等, 比例大致相同。 PMHSS是一個包含21個項目的測量, 旨在評估軍事醫療保健提供者在部署時可能遇到的特定醫療壓力的影響。對PMHSS的探索性因素分析顯示存在兩個不同的因素:可訓練的和無用的壓力因素。驗證性因素分析顯示, 雙因素模型最能代表數據, 所有項目相對於其特定的子量表因素而言, 在一般因素上的載荷更高。證據顯示性別影響局部標量的不變性。PMHSS與一些融合性的測量方法有明顯的相關性, 包括對創傷後壓力症(PTSD)、抑鬱症嚴重程度、由於戰鬥暴露和一般部署相關問題而造成的痛苦, 以及積極情緒的評估, rs =0.30‐0.59。與男性相比, 女性的PMHSS分數與創傷後壓力症和抑鬱症有更強的相關性, 並且在預測收斂測量方面提供了比其他相關結構更高的效度。醫療保健特定的壓力源是一個有待研究的領域, 該研究為與部署相關的護理壓力如何影響部署的軍事醫療人員提供了新的見解, 而不受戰鬥經驗的影響。 Simplified Chinese 军事医疗保健压力感知量表的因素结构及其相关研究 摘要 : 本研究以部署在伊拉克巴拉德联合基地的现役军事医务人员(N = 1, 131)为样本, 评估了军事医疗保健压力感知量表(PMHSS)的因素结构、信度估计、相关性以及预测效用。该样本由男性(51.2%)和女性(48.8%)组成, 年龄从18岁到60岁不等, 比例大致相同。 PMHSS是一个包含21个项目的测量, 旨在评估军事医疗保健提供者在部署时可能遇到的特定医疗压力的影响。对PMHSS的探索性因素分析显示存在两个不同的因素:可训练的和无用的压力因素。验证性因素分析显示, 双因素模型最能代表数据, 所有项目相对于其特定的子量表因素而言, 在一般因素上的载荷更高。证据显示性别影响局部标量的不变性。PMHSS与一些融合性的测量方法有明显的相关性, 包括对创伤后压力症(PTSD)、抑郁症严重程度、由于战斗暴露和一般部署相关问题而造成的痛苦, 以及积极情绪的评估, rs =0.30‐0.59。与男性相比, 女性的PMHSS分数与创伤后压力症和抑郁症有更强的相关性, 并且在预测收敛测量方面提供了比其他相关结构更高的效度。医疗保健特定的压力源是一个有待研究的领域, 该研究为与部署相关的护理压力如何影响部署的军事医疗人员提供了新的见解, 而不受战斗经验的影响。